EFFECTS OF PLANTER VIBRATION ON BALANCE AND POSTURAL INSTABLITY IN CHRONIC STROKE PATIENTS (The Research of Medical Science Review, 2024)
To determine the effect of planter vibration on balance and postural control in chronic stroke patients. The randomized controlled trial (RCT) was conducted from June 2021 to September 2021. Thirty-six patients were divided into two groups on the basis of toss and coin method. The inclusion criteria were both gender of age between 40 years to 70 years, participants who had their first ever stroke ≥ 6 months ago, medically stable, able to walk without use of walking aids, Rankin Modified Scale 4 score and able to understand verbal commands. Participations in other treatment protocols for balance, presence of other neurological or musculoskeletal conditions affecting balance, history of fracture or lower-limb surgery within the 12 months, having vestibular, visual or auditory disorders were excluded from study. The outcomes of study were berg balance scale, the Modified of the Postural Assessment Scale for Stroke Patients (PASS) and Stroke Specific Quality of Life Scale (SS-QOL). Measurements were taken at baseline and after six weeks of intervention. Data was analyzed using SPSS 21.The overall mean ages was 63.62±7.31years. Of 32 participants, 21 (66%) male and 11 (34%) female participants completed the study. Experimental group showed significantly better results for BBS, SS-QOL and M-PASS values (p< 0.05 each). Planter vibration training along with conventional physiotherapy treatment had better outcome as compared to only conventional physiotherapy treatment on balance, postural control and quality life of in chronic stroke patients.